Personality traits of a sample of high school students in Laghouat city - MOUATTAH, Nasira; ARAR, Samia (Social Sciences Journal, 2022)
The current study aims to try to identify the most important personality traits of a sample of high school students in Laghouat, as well as the differences between students in terms of personality traits according to the gender variable. The study sample comprising 120 students, 55 of which were males and 65 were females, selected by the stratified random sampling method and according to the descriptive approach. To achieve the objectives of the study, the Freiburg Scale of personality traits, expressed by Muhammad Hassan Allawi, was used. Concerning the statistical methods adopted in this study, the parametric technique was used through the program Statistical Package for the Social Sciences SPSS version 22. Following the statistical treatment, the results showed that the high school students have a high degree of social characteristics, an intermediate of calmness, excitability, depression, domination and control characteristics, a low degree of neuroticism and aggression characteristics. No difference was detected between the males and females in the personality traits, except for the characteristics of neuroticism and control favoring the females and the characteristic of domination favoring the males.